PENGARUH PEMBELAJARAN BERBASIS MASALAH DAN INKUIRI TERBIMBING TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN KREATIF SISWA - sohibi, Muh; siswanto, joko (Jurnal Penelitian Pembelajaran Fisika, 2012)
ABSTRACT The purpose of this study was to determine whether the use of problem-based learning model provides a better effect than on guided inquiry and expository on critical and creative thinking skills of students in SMA N 1 Comal Pemalang 2012/2013. The experiment was conducted from 31 July 2012 until 10 August 2012. The study population was all class X which amounts to 9 classes. Samples taken are three classes, namely X-5 as the control group, a class X-6 as the experimental group 1 and Class X-7 as the experimental group 2. The final analysis using t-test (right side), for students critical skills: the first experimental class and control: tcount> ttable = 4.64> 2.00, the experimental class 2 and control: tcount> ttable = 2.37 > 2.00 and the class experiment 1 and experiment 2: tcount> ttable = 2.68> 1.99. For the critical skills of students in the experimental class 1 and control: tcount> ttable = 4.41> 2.00, the experimental class 2 and control: tcount> ttable = 5.29> 2.00 and the class experiment 1 and experiment 2 : tcount> ttable = 2.27> 1.99. From these results it can be concluded that the experimental class one that uses problem based learning give influence better than both the other classes using guided inquiry and expository on the ability of students to think critically and creatively. Keywords: problem-based learning, guided inquiry, critical thinking and creative students.